2006
DOI: 10.1086/502976
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Treatment‐Related Predictors of Thymidine‐Analogue Mutation Patterns in HIV‐1 Isolates after Unsuccessful Antiretroviral Therapy

Abstract: We investigated, in patients tested between 1991 and 2004, the patterns of mutually exclusive human immunodeficiency virus-1 thymidine-analogue mutations (TAMs) in 4039 reverse-transcriptase sequences with > or = 1 TAM. TAM pattern 1, which included M41L and L210W and excluded K70R and is coupled with more-extensive cross-resistance to drugs, became the most frequent pattern after 1996. In 1465 genotypes from 684 patients in whom highly active antiretroviral therapy (HAART) was unsuccessful, predictors of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 12 publications
3
19
0
Order By: Relevance
“…However, geometrical constraints arising from the different conformation of the ZDVMP moiety in the binary complex could also affect the removal of the inhibitor. Our results also support previous reports showing that Tyr-208, Lys-211 and Phe-214 substitutions, despite lacking a direct effect on drug resistance per se, could increase ZDV resistance and cross-resistance when they appear in combination with amino acid substitutions of the TAM1 pathway (7,23,28).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, geometrical constraints arising from the different conformation of the ZDVMP moiety in the binary complex could also affect the removal of the inhibitor. Our results also support previous reports showing that Tyr-208, Lys-211 and Phe-214 substitutions, despite lacking a direct effect on drug resistance per se, could increase ZDV resistance and cross-resistance when they appear in combination with amino acid substitutions of the TAM1 pathway (7,23,28).…”
Section: Discussionsupporting
confidence: 92%
“…This effect could be due to the fact that Leu-214 somehow inhibits the development of TAM1. It has been reported that this mutational profile confers higher phenotypic resistance to NRTIs than TAM2, thus providing a favorable effect on virological response (6,7,15,26). Moreover, our results suggest that Leu-214 not only influences viral fitness but could also play a direct role in drug susceptibility.…”
Section: Discussionsupporting
confidence: 54%
“…TAMs are common in low income countries in which the fixed-dose combinations containing thymidine analogues are the mainstay of therapy (Ross et al, 2001). TAMs are also common in HIV-1 isolates from patients who began therapy in the pre-highly active antiretroviral therapy (HAART) era (De Luca et al, 2006;Rhee et al, 2005). The mutations accumulate in two distinct but overlapping patterns (De Luca et al, 2006;Gonzales et al, 2003;Marcelin et al, 2004b;Yahi et al, 1999).…”
Section: Nrti Tams (Excision)mentioning
confidence: 99%
“…TAMs are also common in HIV-1 isolates from patients who began therapy in the pre-highly active antiretroviral therapy (HAART) era (De Luca et al, 2006;Rhee et al, 2005). The mutations accumulate in two distinct but overlapping patterns (De Luca et al, 2006;Gonzales et al, 2003;Marcelin et al, 2004b;Yahi et al, 1999). The type I pattern includes the M41L, L210W and T15Y mutations, respectively (De Luca et al, 2006;Miller et al, 2004).…”
Section: Nrti Tams (Excision)mentioning
confidence: 99%
See 1 more Smart Citation